Aksioma Ideal Electronical Government di Era Informasi dan Keterbukaan (Studi pada Dinas Komunikasi dan Informatika Kota Surabaya) - Ilyas, Taufiq Rahman (Universitas 17 Agustus 1945 Surabaya, 2019)
The Axiom ofÂ The Ideal Electronic Government in the information and Openness is when the value of accountability can be aligned with the meaning of transparency (openness), Then the process of public service runs effectively and efficiently where facilities and the existence of public service based on information technology (especially city scale) are available. Which is supported by increasing public use of communication and information channels.Keyword : Axiom, Ideal, Electronic Government, informatioan and Openness